1992
DOI: 10.1016/0736-5748(92)90030-4
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of vestibular function in young guinea pigs after streptomycin treatment. Glutamate decarboxylase activity and nystagmus response assessment

Abstract: Fifty-day streptomycin (STP) treatment in guinea pigs causes specific vestibular hair cell (VHC) types I and II (HCI; HCII) degeneration, depletion of glutamate decarboxylase (GAD) and a gradual disappearance of postrotatory nystagmus response (PRNR), which is a sign of vestibular function alteration. In order to look for a possible spontaneous reversibility and its time course guinea pigs receiving 300 mg/kg STP daily were monitored for PRNR and vestibular GAD loss. Once PRNR was lost, STP was interrupted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Damaged, but surviving, hair cells may be found after systemic treatments where the levels of aminoglycosides are sufficiently weak as to not kill the animals from nephrotoxicity. Taken together, the observations suggest the possibility that loss and replacement of hair bundles may occur in humans and could potentially contribute to previously unexplained delayed recovery of auditory and vestibular sensitivity in mammals after treatments with ototoxic antibiotics (Black et al, 1987;Nicol et al, 1992;Meza et al, 1992). Such cellular repair might also explain delayed recovery of hearing thresholds after certain types of noise exposure, a phenomenon that is reported to continue for days (Mills et al, 1970).…”
Section: Discussionmentioning
confidence: 76%
“…Damaged, but surviving, hair cells may be found after systemic treatments where the levels of aminoglycosides are sufficiently weak as to not kill the animals from nephrotoxicity. Taken together, the observations suggest the possibility that loss and replacement of hair bundles may occur in humans and could potentially contribute to previously unexplained delayed recovery of auditory and vestibular sensitivity in mammals after treatments with ototoxic antibiotics (Black et al, 1987;Nicol et al, 1992;Meza et al, 1992). Such cellular repair might also explain delayed recovery of hearing thresholds after certain types of noise exposure, a phenomenon that is reported to continue for days (Mills et al, 1970).…”
Section: Discussionmentioning
confidence: 76%
“…In mammals, although morphological evidence is available pointing to regeneration of hair cells Warchol et al, 1993;Sobkowicz et al, 1996;Lopez et al, 1997;Zheng et al, 1999] functional recovery was not confirmed using direct end-organ parameters. Studies that had shown functional recovery after ototoxic treatment used functional parameters that were (partially) based on central compensation [Meza et al, 1992[Meza et al, , 1996Taura et al, 2006;Staecker et al, 2007]. In this study we used parameters of direct end-organ function, so the effects of central compensation did not bias the longerterm results.…”
Section: Long-term Effect Of Gentamicin Treatmentmentioning
confidence: 99%
“…In a recent study where type-I hair cell regeneration was induced with Math1 gene transfer, it was shown that the appearance of the new type-I hair cells was not normal [Xu et al, 2012]. Whether vestibular function may recover in mammals as a result of hair cell regeneration is thus an important question, and this has been addressed by only a few studies [Meza et al, 1992[Meza et al, , 1996Taura et al, 2006]. Meza et al [1992] showed recovery of vestibular function in guinea pigs treated with streptomycin by assessing nystagmus responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested for some time that aminoglycoside drugs are ototoxic [2]. Data from reports of research in animals [11] and some studies carried on in human infants support these results [1,4]. Data from reports of research in animals [11] and some studies carried on in human infants support these results [1,4].…”
Section: Introductionmentioning
confidence: 97%